Controls on compactional behavior and reservoir quality in a Triassic Buntsandstein reservoir, Upper Rhine Graben, SW Germany. (February 2022) - Busch, Benjamin; Adelmann, Dirk; Herrmann, Rolf; Hilgers, Christoph
Abstract: The main reservoir quality controls in Triassic Buntsandstein deposits in the Upper Rhine Graben and surrounding outcrops in Germany and France are discussed to be authigenic mineral precipitates and the vicinity to structural elements (faults and fractures). To better understand reservoir quality controls in this lithology, a detailed diagenetic study based on petrographic methods (optical and SEM) in combination with petrophysical measurements (porosity and permeability) on core material (1133–1591 m TVD) was initiated. This case study highlights that large detrital grain sizes and low compactional porosity loss in association with blocky authigenic cements such as quartz and dolomite are beneficial to reservoir quality, whereas variable illite textures have a dual, but opposite effect on reservoir qualities. Grain coating illite (tangential and radial) may preserve intergranular porosity by inhibition of syntaxial quartz precipitation, while at the same time, if present at grain contacts, tangential illite enhances chemical compaction and reduces the available intergranular volume. The presence of early diagenetic carbonate cemented nodules is also beneficial for reservoir quality in stabilizing the grain framework against compactive porosity loss. Overall, detrital grain size and the intergranular volume, as a result of compaction and cementation, are derived as the main reservoir quality controls. The formation of hydrothermally mineralized veins prior to hydrocarbon charging does not show a distinct impact on porosity and permeability in the sandstone matrix. Fractures and interstices between vein minerals such as barite, galena, tetrahedrite, and siderite are equally covered in hydrocarbon residue, as are all present detrital and authigenic minerals in the sandstones indicating that vein precipitates, if not pervasive, do not alter the overall reservoir quality. This study may indicate additional potential to identify high reservoir quality intervals in the studied succession. Highlights: Compaction and detrital grain size control RQ in studied Buntsandstein samples. Quartz and dolomite cements counteract compaction. Blocky cements (syntaxial quartz, dolomite nodules) preserve RQ. Tangential illitic grain coatings enhance chemical compaction, reducing RQ.